2015
DOI: 10.15713/ins.jcri.77
|View full text |Cite
|
Sign up to set email alerts
|

Regional variation in incisor shoveling in Indian population

Abstract: Background:The forensic odontologists play a very important role in assisting the Forensic team in the identification of corpuses found in natural disasters and homicides. Since tooth is a calcified structure and is resistant to high or low temperatures and is adequately strong to resist trauma, the teeth may be the only structure left behind intact in most of the cases. The resemblance of incisors to a shovel results from the combination of a concave lingual surface and elevated marginal ridges of the incisor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Shoveling was noted considerably in Mongoloid groups, including north-eastern Indians, Bunun aborigines, Chinese, and Eskimos. A study carried out by Canger E.M et al, in 2014 and Uthaman C et al, in the year 2015 and Nagraj T et al, in 2015 revealed that shoveling was seen in 10.1%, 40%, and 85% in Turkis, Tibetians, and Western Indian populations respectively [13][14][15] . In the current study, shoveling accounted for 8.3% of the subjects.…”
Section: Discussionmentioning
confidence: 97%
“…Shoveling was noted considerably in Mongoloid groups, including north-eastern Indians, Bunun aborigines, Chinese, and Eskimos. A study carried out by Canger E.M et al, in 2014 and Uthaman C et al, in the year 2015 and Nagraj T et al, in 2015 revealed that shoveling was seen in 10.1%, 40%, and 85% in Turkis, Tibetians, and Western Indian populations respectively [13][14][15] . In the current study, shoveling accounted for 8.3% of the subjects.…”
Section: Discussionmentioning
confidence: 97%
“…These studies were done on plaster models, direct clinical assessment, radiographs or digital photographs. [ 6 7 8 9 10 11 12 ]…”
Section: Introductionmentioning
confidence: 99%